2019
DOI: 10.1073/pnas.1905617116
|View full text |Cite
|
Sign up to set email alerts
|

Subgenomic flavivirus RNA binds the mosquito DEAD/H-box helicase ME31B and determines Zika virus transmission by Aedes aegypti

Abstract: Zika virus (ZIKV) is an arthropod-borne flavivirus predominantly transmitted by Aedes aegypti mosquitoes and poses a global human health threat. All flaviviruses, including those that exclusively replicate in mosquitoes, produce a highly abundant, noncoding subgenomic flavivirus RNA (sfRNA) in infected cells, which implies an important function of sfRNA during mosquito infection. Currently, the role of sfRNA in flavivirus transmission by mosquitoes is not well understood. Here, we demonstrate that an sfRNA-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 66 publications
1
75
0
Order By: Relevance
“…Bunyaviruses snatch mRNA caps from host transcripts in P bodies, and thus cellular factors such as DDX6, which promote the decapping of host mRNAs and thereby deplete the pool of capped RNAs in P bodies, attenuate bunyaviral infection including La Crosse virus (LACV) and RVFV [40]. In mosquitoes, DDX6 is antiviral against the flaviviruses West Nile virus and Zika virus and is counteracted by the noncoding sfRNA derived from the flavivirus 3 UTR, which binds to DDX6 and sequesters it [67]. Human DDX6 is similarly antiviral against ZIKV and is sequestered by sfRNA [68].…”
Section: P-body and Stress Granule Helicases In Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bunyaviruses snatch mRNA caps from host transcripts in P bodies, and thus cellular factors such as DDX6, which promote the decapping of host mRNAs and thereby deplete the pool of capped RNAs in P bodies, attenuate bunyaviral infection including La Crosse virus (LACV) and RVFV [40]. In mosquitoes, DDX6 is antiviral against the flaviviruses West Nile virus and Zika virus and is counteracted by the noncoding sfRNA derived from the flavivirus 3 UTR, which binds to DDX6 and sequesters it [67]. Human DDX6 is similarly antiviral against ZIKV and is sequestered by sfRNA [68].…”
Section: P-body and Stress Granule Helicases In Viral Infectionmentioning
confidence: 99%
“…IBV [81] dsRNA sensing (with DDX21 and DHX36) [21] Transmissible gastroenteritis virus [18] NF-κB signaling [19] DDX3X Arenavirus [38] JEV [47] HIV [74,84] IFN-β induction (with TBK1) [26] Innate immune signaling [27,28] HBV [36,93] Myxoma virus [88] VACV K7 [34] HBV polymerase [35] HCV 3 UTR [37] DDX5 JEV [47] HIV [84] Myxoma virus [88] DDX6 Negative regulation of ISG induction [66] RVFV, LACV [40] IVB [65] Flaviviruses: sequestered by sfRNA [67,68] DDX10 HIV [89] DDX17 HIV [84,94] RVFV [41] Cofactor for ZAP [43] Tombusviruses [45] DDX18…”
Section: Ddx1mentioning
confidence: 99%
“…We speculate that these viral small RNAs from hotspots could derive from secondary structure of the virus rather than replication intermediates: DCR2 could cleave the hairpin structure of viral RNAs and the loop structure adjacent to the cleavage site might result in 26-30 nt long small RNAs as by-product of vsiRNAs production. Interestingly, previous studies suggested that the subgenomic RNA of flaviviruses, which corresponds to the 3’ UTR, is capable of supressing the RNAi machinery, possibly as an RNA decoy or by inhibiting the loading of vsiRNA into the RISC [21, 23, 24]. The high amount of siRNAs from the the 3’ UTR of AEFV could be a strategy from the virus to escape from the siRNA pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The siRNA duplexes are loaded into the RNA-induced silencing complex (RISC) containing Argonaute2 (Ago2) that cleaves the target viral RNA under the guide of siRNA. Some mosquito viruses have evolved avoidance mechanisms to the siRNA pathway, demonstrating that virus-derived siRNAs (vsiRNAs) play an important antiviral function in mosquito vectors [19-24].…”
Section: Introductionmentioning
confidence: 99%
“…sfRNAs have been associated with pathogenic outcomes and cytopathicity during infection (Funk et al 2010;Chang et al 2013;Walker et al 2013;Donald et al 2016;Filomatori et al 2017;Junglen et al 2017). Although their full set of functions remains an active area of investigation (Slonchak and Khromykh 2018) sfRNAs have been shown to bind a number of host proteins (Bidet et al 2014;Schnettler et al 2014;Manokaran et al 2015;Moon et al 2015;Goertz et al 2019;Michalski et al 2019) suggesting they affect several processes during infection including inhibiting the interferon response (Schuessler et al 2012) and suppressing RNAi pathways in insects (Schnettler et al 2012;Schnettler et al 2014;Moon et al 2015). Furthermore, there is evidence that sfRNAs are involved in switching between insect vectors and mammalian hosts (Filomatori et al 2017;de Borba et al 2019), enhancing transmission by mosquitoes (Pompon et al 2017;Yeh and Pompon 2018;Goertz et al 2019;Slonchak et al 2020), and altering the cell's mRNA decay program (Moon et al 2012;Michalski et al 2019).…”
Section: Introductionmentioning
confidence: 99%